Do lump-sum investing strategies really outperform dollar-cost averaging strategies?. Issue 3 (23rd July 2020) - Lu, Richard; Hoang, Vu Tran; Wong, Wing-Keung
Abstract : Purpose: The literature has demonstrated that lump-sum (LS) outperforms dollar-cost averaging (DCA) in uptrend markets while DCA outperforms LS only when the asset price is mean-reverted or downtrend. To bridge the gap in the literature, this study aims to use both Sharpe ratio (SR) and economic performance measure (EPM) to compare the performance of DCA and LS under both accumulative and disaccumulative approaches when the asset price is simulated to be uptrend. Design/methodology/approach: This study uses both disaccumulative and accumulative approaches to compare DCA with LS and uses both SR and EPM to evaluate their performance when the asset price is simulated to be uptrend. Instead of using the annualized returns that are commonly used by other DCA studies, we compute the holding-period returns in the comparison in this paper. Findings: The simulation shows that no matter which approach is used, DCA outperforms LS in nearly all the cases in the less uptrend markets while DCA still performs better than LS in many cases of the uptrend markets, especially when the market is more volatile and investment horizon is long, regardless which approach the authors used. The authors also find more evidence supporting DCA over LS by using EPM, which is more suitable in the analysis because the returns generated by DCA are positive skewed and flat-tailed that are ignored when SR is used. Research limitations/implications: The authors conclude that DCA is a better trading strategy than LS for investment even in the uptrend market, especially on high risky assets. Practical implications: Investors could consider choosing DCA instead of LS as their trading strategy, especially when they prefer long term investment and investing in high-risk assets. Social implications: Fund managers could consider recommending DCA to their customers, especially when they prefer long term investment and investing in high-risk assets. Originality/value: This is the own study and, as far as the authors know, this is the first study in the literature uses both SR and EPM to compare the performance of DCA and LS under both accumulative and disaccumulative approaches when the asset price is simulated to be uptrend.